Interdiffusion and barrier layer formation in thermally evaporated Mn/Cu heterostructures on SiO2 substrates - Lozano, J; Lozano-Perez, S; Bogan, J; Wang, Y; Brennan, B; Nellist, P; Hughes, G (2011)
Mn/Cu heterostructures thermally evaporated onto SiO2 and, subsequently, annealed were investigated by transmission electron microscopy related techniques in order to study the diffusion interactions which lead to barrier layer formation. Energy dispersive x-ray spectroscopy and electron energy loss spectroscopy provide evidence for the interdiffusion between the Mn and Cu layers following a 450°C anneal, where the Mn diffuses toward the surface of the structure, while Cu diffuses toward the Mn/ SiO2 but does not propagate into the dielectric. The chemical composition of the 2-3 nm interfacial layer is primarily a mixture of +2 and +3 Mn valences, in good agreement with previously reported results. © 2011 American Institute of Physics.